Evaluation of different taste sensations along with body mass index (BMI) in geriatric patients with and without complete dentures - Vidya G. Doddawad; Farina Mehrin; K. N. Raghavendraswamy; Smitha M. Chandrashekarappa; S. Shivananda; C. S. Vidya (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The purpose of this study was to investigate the effect of acrylic full removable dentures on the perception of four primary tastes (sweet, sour, salty, and bitter), as well as to determine if there is a correlation between changes in body mass index (BMI) and taste perception. MATERIALS AND METHODS: A total of 60 patients who wore acrylic removable dentures and 60 controls were included in the study as a convenient sample. Sixteen solutions for basic tastes were prepared, and the patients were asked to identify the taste of each solution from the lowest concentration. Anthropometric measures, such as height and weight, were measured and recorded in an MS-Excel sheet. The data were analyzed using SPSS version 23. RESULTS: The results showed that patients with complete removable dentures had lower taste scores for sourness (P < 0.001) and sweetness (P < 0.001) compared to the control group. However, there was no significant difference in salt taste scores (P = 0.218) and bitterness (P = 0.002) between the two groups. Additionally, the study found a correlation between lower BMI values and higher taste scores among denture-wearing patients, indicating an inverse relationship between total taste scores and BMI. CONCLUSIONS: The study suggests that geriatric patients with complete dentures have reduced taste sensations compared to those without dentures which can have a negative impact on their nutritional status. Therefore, it is crucial to provide adequate nutritional support and dietary counseling for geriatric patients based on health policy to maintain their overall health and well-being.